Bioconjugate techniques - Hermanson, Greg T. (Academic Press is an imprint of Elsevier, 2013)
Bioconjugate Techniques, 3rd Edition, is the essential guide to the modification and cross linking of biomolecules for use in research, diagnostics, and therapeutics. It provides highly detailed information on the chemistry, reagent systems, and practical applications for creating labeled or conjugate molecules. It also describes dozens of reactions, with details on hundreds of commercially available reagents and the use of these reagents for modifying or crosslinking peptides and proteins, sugars and polysaccharides, nucleic acids and oligonucleotides, lipids, and synthetic polymers. *Offers a one-stop source for proven methods and protocols for synthesizing bioconjugates in the lab *Provides step-by-step presentation makes the book an ideal source for researchers who are less familiar with the synthesis of bioconjugates *Features full color illustrations *Includes a more extensive introduction into the vast field of bioconjugation and one of the most thorough overviews of immobilization chemistry ever presented.